2017
DOI: 10.1021/acs.biochem.7b00614
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Enzymology: Web Tools for Leveraging Protein Family Sequence–Function Space and Genome Context to Discover Novel Functions

Abstract: The exponentially increasing number of protein and nucleic acid sequences provides opportunities to discover novel enzymes, metabolic pathways, and metabolites/natural products, thereby adding to our knowledge of biochemistry and biology. The challenge has evolved from generating sequence information to mining the databases to integrating and leveraging the available information, i.e., the availability of “genomic enzymology” web tools. Web tools that allow identification of biosynthetic gene clusters are wide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
173
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(178 citation statements)
references
References 103 publications
1
173
0
Order By: Relevance
“…However, the use of Pythoscape requires knowledge of programming as well access to a computer cluster. The Enzyme Function Initiative (EFI [15]) developed and provides a “democratized,” i.e., publicly accessible, web tool for generating SSNs, the EFI-Enzyme Similarity Tool (EFI-EST; https://efi.igb.illinois.edu/efi-est/ [12,16]). Using EFI-EST, SSNs can be constructed for Pfam and/or InterPro families (and/or user-defined sets of sequences).…”
Section: Sequence Similarity Network (Ssns): Sequence-function Spacementioning
confidence: 99%
See 1 more Smart Citation
“…However, the use of Pythoscape requires knowledge of programming as well access to a computer cluster. The Enzyme Function Initiative (EFI [15]) developed and provides a “democratized,” i.e., publicly accessible, web tool for generating SSNs, the EFI-Enzyme Similarity Tool (EFI-EST; https://efi.igb.illinois.edu/efi-est/ [12,16]). Using EFI-EST, SSNs can be constructed for Pfam and/or InterPro families (and/or user-defined sets of sequences).…”
Section: Sequence Similarity Network (Ssns): Sequence-function Spacementioning
confidence: 99%
“…The EFI also offers the democratized EFI-Genome Neighborhood Tool (EFI-GNT; https://efi.igb.illinois.edu/efi-gnt/[12]) that provides statistical analysis of genome context for bacterial and fungal members of protein families to identify possible functional linkage, e.g., metabolic pathways. Each sequence in an input SSN is used to query its genome neighborhood.…”
Section: Genome Neighborhood Network (Gnns): Genome Context To Identmentioning
confidence: 99%
“…To identify other possible low molecular weight transpeptidases, we generated a sequence similarity network (SSN) for the Peptidase S11 family (Figures 2, S2). 8 The alignment analysis was restricted to only the catalytic domain of the family members. We found that Sa PBP4 and PBPs from at least 40 other Gram-positive bacteria (Table S2) clustered into two related groups that were separated from a much larger group containing known hydrolases, including E. coli PBP5 ( Ec PBP5), a well-characterized carboxypeptidase.…”
mentioning
confidence: 99%
“…We sought to gain more quantifiable information about whether sub-families of DUF560 homologs exist and whether DUF560 are enriched among mucosal symbionts. A sequence similarity network of DUF560 homologs was generated using the Enzyme Function Initiative (EFI) [33][34][35][36] (Fig. 2) and manually annotated using publicly available database entry information to highlight either the environmental source ( Fig.…”
Section: Duf560 Protein Sub-families Exist and Are Correlated With LImentioning
confidence: 99%